EXPLICITATION AND IMPLICITATION IN THE LITERATURE TRANSLATION FOR CHILDREN - Ni Made Diana Erfiani (LITERA : Jurnal Bahasa Dan Sastra, 2017)
ABSTRACT This paper aims at investigating the occurrence of explicitation and implicitation in literarytranslation especially for children. The analysis focuses on determining the criteria, comparingthe degree of the two concepts, and finding the types of explicitation . The object to be investigated is a unidirectional parallel corpora of literature translation namely English FairyTale Vivia’s Undersea Adventure with its Indonesian translation Petualangan Vivia di Bawah Laut. The result of the analysis shows that in terms of criteria, literature translation for childrenshows slightly higher degree in explicitation compared with implicitation. The insignificantdegree of differentiation between the two concepts indicates that they occur as a “twin concept” that cannot be separated one another. It also deals with the feature of translationsituation which tends to explicate implicit messages in translation processes in order to make it easier to comprehend. In terms of type of explicitation, the analysis reveals that there are threetypes of explicitation occur in the literary translation for children namely obligatory, optional,and pragmatic types of explicitation. Keywords: explicitation, implicitation, twin concept, children literature  ABSTRAK Tulisan ini bertujuan untuk menyelidiki kemunculan konsep eksplisitasi dan implisitasi padaterjemahan sastra terutama untuk anak-anak. Analisis berfokus pada penentuan kriteria, perbandingan tingkat kemunculan kedua konsep, serta penentuan tipe eksplisitasi karyaterjemahan. Obyek yang diteliti adalah korpora paralel searah karya sastra dalam bahasa Inggris yaitu dongeng yang berjudul Vivia’s Undersea Adventure yang diterjemahkan kedalam bahasa Indonesia Petualangan Vivia di Bawah Laut. Hasil analisis menunjukkan bahwa dalam hal kriteria, hanya terdapat sedikit perbedaan antara tingkat kemunculan ekslpisitasidan implisitasi dalam terjemahan karya sastra anak-anak. Perbedaan yang tidak signifikanmenunjukkan bahwa eksplisitasi dan implisitasi merupakan “konsep kembar” yang tidak dapat dipisahkan satu dengan lainnya. Hal ini terkait pula dengan fitur terjemahan yang cenderungmenunjukkan upaya untuk menjelaskan pesan yang masih implisit sehingga teks lebih mudah untuk dipahami. Dalam hal tipe, hasil analisis menunjukkan bahwa terdapat tiga tipeeksplisitasi dalam terjemahan sastra anak-anak yaitu obligatori, opsional, dan pragmatik. Kata kunci: eksplisitasi, implisitasi, konsep kembar